Plasma enhanced chemical vapor deposition of titanium(IV) ethoxide-oxygen-helium mixtures - Durrant, Steven F. [UNESP]; da Cruz, Nilson C. [UNESP]; Rangel, Elidiane C. [UNESP]; de Moraes, Mario A. Bica (Elsevier B.V. Sa, 2008)
Thin films were deposited by plasma enhanced chemical vapor deposition from titanium (IV) ethoxide (TEOT)-oxygen-helium mixtures. Actinometric optical emission spectroscopy was used to obtain the relative plasma concentrations of the species H, CH, O and CO as a function of the percentage of oxygen in the feed, R(ox). The concentrations of these species rise with increasing R(ox) and tend to fall for R(ox) greater than about 45%. As revealed by a strong decline in the emission intensity of the actinometer Ar as R(ox) was increased, the electron mean energy or density (or both) decreased as greater proportions of oxygen were fed to the chamber. This must tend to reduce gas-phase fragmentation of the monomer by plasma electrons. As the TEOT flow rate was fixed, however, and since the species H and CH do not contain oxygen, the rise in their plasma concentrations with increasing R(ox) is explained only by intermediate reactions involving oxygen or oxygen-containing species. Transmission infrared (IRS) and X-ray photoelectron (XPS) spectroscopies were employed to investigate film structure and composition. The presence of CH(2), CH(3), C=C, C-O and C=O groups was revealed by IRS. In addition, the presence of C-O and C=O groups was confirmed by XPS, which also revealed titanium in the +4 valence state. The Ti content of the films, however, was found to be much less than that of the monomer material itself. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: tetra-ethoxy-titanium; thin films; PECVD; actinometry; IRS; XPS